Role of fucosyltransferase IV in the migration and invasion of human melanoma cells. Issue 5 (21st January 2020) - Shan, Xiu; Dong, Weijie; Zhang, Li; Cai, Xin; Zhao, Yi; Chen, Qun; Yan, Qiu; Liu, Jiwei
Abstract: Malignant melanoma is one of the most aggressive human tumor types, mainly due to its high invasion capability, metastatic properties, and the absence of effective treatments. Glycosylation serves a pivotal role in the migration and invasion of melanoma. However, differences in glycosylation between high and low metastatic melanoma cells and how these regulate migration and invasion by altering the expression of fucosyltransferases (FUTs) remain unclear. In the present study, matrix‐assisted laser desorption/ionization‐time‐of‐flight‐mass spectrometry (MALDI‐TOF‐MS) analysis revealed that the composition profiling of fucosylated N‐glycans differed between high metastatic C8161 and low metastatic A375P cells. Further analysis revealed that FUT4 expression was significantly increased in C8161 cells. Melanoma tissue arrays further demonstrated that FUT4 was overexpressed in metastatic samples. Altered FUT4 expression was accompanied by a change in the migration and invasion capacity of the cells. In addition, the migration and invasion potential of melanoma cells were decreased in C8161 and increased in A375P cells upon altering FUT4 expression levels by small interfering RNA or complementary DNA transfection. Furthermore, regulating FUT4 expression markedly modulated the activity of the phosphoinositide‐3‐kinase/Akt (PI3K/Akt) signaling pathway, which affected melanoma cell migration and invasion. In conclusion, FUT4 is a novel biomarker and regulator of the migration and invasion of melanoma cells and may serve as a therapeutic target for melanoma.